PELAKSANAAN KURSUS CALON PENGANTIN (AUCATIN) DI KANTOR URUSAN AGAMA ( KUA) KEC. BATANG KAPAS KABUPATEN PESISISR SELATAN - Fadil Maiseptian; Mistra Jamil (Al Irsyad : Jurnal Bimbingan Konseling Islam, 2020)
ABSTRACT The candidate bride course (Suscatin) functions to provide knowledge, understanding, and skills in a short time to the prospective bride and groom about household/family life so that the bride and groom can live as a family in sakinah, mawaddah, warahmah. The purpose of this study was to determine the benefits of the prospective bride course (Suscatin) for the prospective bride and groom and the supporting factors and obstacles to the implementation of the prospective bride course (Suscatin) at KUA Batang Kapas District. This type of research uses field research (field research) with data collection techniques using observation and interviews. The data source of this research is the head of the KUA, extension agents, and future brides. The results of this study are: 1) the benefits of the prospective bride course (Suscatin) for prospective brides at KUA Batang Kapas District are to increase understanding and knowledge of household/family life in realizing family sakinah, mawaddah, warahmah and reducing the number of disputes, divorces, and Domestic violence, 2) the supporting factors for the implementation of the Candidate Bride Course (Suscatin) at KUA Batang Kapas District are the enthusiasm of the participants, competent guides, facilities, and infrastructure. Meanwhile, the inhibiting factors for not implementing the Candidate Bride Course (Suscatin) at the KUA Batang Kapas District are the budget for funds from the government, limited time, lack of participant discipline, some of the materials have not been documented formally from the Ministry of Religion.